Subspeciality or super speciality in paediatric surgery – is it essential or luxury? (Journal of Paediatric Surgeons of Bangladesh, 2018)
Abstract not availableJournal of Paediatric Surgeons of Bangladesh (2016) Vol. 7 (2): 27-28